AN EXAMINATION OF TECHNIQUE OF CULTURAL FISH FARMING IN LAKE CHAD BASIN AREA OF NIGERIA - Zanna, Babagana (Innovare Journal of Life Sciences, 2024)
The study was conducted in Lake Chad Basin area of Nigeria where Fishing has been the occupation of the inhabitants in the study area. The study focused on the cultural technique of fish farming in the study area. Data for the study was obtained from both primary and secondary sources through a public participation and stakeholders’ interview with the application of focus group discussion. The data collection for the research work was carried out within the period of 1st to 31st March 2023. Primarily, conservative qualitative method with snow-ball technique was applied and information was elicited from the respondents on technique of fish farming culture. The study revealed that technique of fish farming culture involves the use culturally believed norms of unsustainable age long intrinsic practice. Recommendation were made for the formulation of policy framework in connection to the cultural technique of fish farming and other related issues for the transformation and sustainability of the culture of fish farming in the study area.